The Lexion Of The African American English In Georgia Doyle Johnson's Frederick Douglas And Loraine Hansberry's A Raisin In The Sun - Sadiq, Nizamuddin (Journal of English and Education (JEE), 2009)
To comprehend that a language belongs to a dialect, one may examine its lexicon. As it is considered non-standard dialect, the American African English lexicon is assumed to have its own characteristic different from the standard American English. Therefore, to gain a better comprehension of the American African English dialect in the view point of lexicon features, the paper will elaborate Georgia Doyle Johnson's Frederick Douglas And Loraine Hansberry's A Raisin In The Sun. This paper is descriptive linguistics rather than a stylistic study as it does not focus on literary style. The data taken was classified into linguistic elements and was tested to the theories of informal English in general; African American English in particular and Standard American English rules of pronunciation. The research findings were summarized and discussed to conclude the research. The result of the research demonstrates that African American English, a variant of informal English, is different from the rules of Standard American English. In terms of lexicon, African American English employs local and rude words. The presence of slang and colloquialisms, taboo words and swearing make it distinctively informal.